PENGARUH MODEL COOPERATIVE LEARNING TIPE STRUCTURED NUMBERED HEADS TERHADAP KEMAMPUAN KOGNITIF SISWA - Ayendra Wahyuni; Syaiful M; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2014)
The purpose of this research to find out  influence  of cooperative learning models of type stuctured numbered heads that impact cognitive abilities of students in the eighth grade social studies at the semester SMP Gajah Mada B.Lampung. The method used in this research is descriptive method . Amount the population of  this research  200 students in the sample amounted to 40 students. The data obtained through testing, observation , documentation and literature , with descriptive statistical data analysis techniques used formula persentase. Based on the analysis of data obtained from the research and explanation, it can be seen that the influence of the type of cooperative learning models Stuctured Numbered Heads positive effect on the improvement of students' cognitive abilities in social studies classes SMP Gajah Mada Bandar Lampung. Penelitian ini bertujuan untuk mengetahui pengaruh  model cooperative learning tipe stuctured numbered heads terhadap kemampuan  kognitif siswa pada mata pelajaran IPS kelas VIII semester ganjil di SMP Gajah Mada B.Lampung. Metode yang digunakan dalam penelitian ini adalah metode diskriptif. Populasi penelitian berjumlah 200 siswa dengan sampel berjumlah 40 siswa. Data diperoleh melalui tes, observasi, dokumentasi dan kepustakaan, dengan teknik analisis data statistik diskriptif dengan munggunakan rumus persentase.Berdasarkan analisis data yang diperoleh dari hasil penelitian dan pembahasan,  maka dapat diketahui bahwa model Cooperative Learning tipe Stuctured Numbered Heads berpengaruh positif terhadap peningkatan kemampuan kognitif siswa pada mata pelajaran IPS kelas VIII SMP Gajah Mada Bandar Lampung. Kata kunci: IPS, kemampuan kognitif, stuctured numbered heads